Rubber composition and conveyor belt

By optimizing the component ratio of the rubber composition and adding specific types and proportions of rubber, flame retardant and carbon black, the shortcomings of the existing rubber composition in terms of power saving, bending resistance and flame retardant after aging are solved, and a high-performance vulcanized rubber composition is achieved.

CN119823455APending Publication Date: 2025-04-15THE YOKOHAMA RUBBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406444.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-25
Filing Date
2024-10-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing rubber composition for conveyor belts has shortcomings in terms of power saving, bending resistance and flame retardancy after aging, especially the power saving of vulcanized rubber.

Method used

The composition ratio is optimized to improve the performance of the rubber by adding a specific proportion of natural rubber, butadiene rubber, chlorinated paraffin, antimony trioxide, carbon black, sulfur and vulcanization accelerator to the rubber composition.

Benefits of technology

It achieves excellent power saving, bending resistance and flame retardancy of vulcanized rubber, which meets the needs of high-performance conveyor belts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention addresses the problem of providing a rubber composition which enables the resulting vulcanized rubber to have excellent power saving properties, bending resistance, and flame retardancy after aging. The solution is a rubber composition and a conveyor belt manufactured by using the rubber composition. The rubber composition contains a diene rubber including natural rubber and butadiene rubber, a flame retardant including chlorinated paraffin and antimony trioxide, carbon black X including carbon black x1 having a nitrogen adsorption specific surface area of 60-100 m2 / g and a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g, sulfur, and a vulcanization accelerator. The mass ratio of the natural rubber content to the butadiene rubber content is 50 / 50-20 / 80, the carbon black X content is 55-80 parts by mass with respect to 100 parts by mass of the diene rubber, and the chlorinated paraffin content is 35% by mass or more of the butadiene rubber content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition and a conveyor belt. Background Art

[0002] Conventionally, there is known a rubber composition for a conveyor belt containing natural rubber, butadiene rubber, chlorinated paraffin, antimony trioxide, and the like (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 7182853 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Conveyor belts are required to have excellent power saving, bending resistance, flame retardancy after aging assuming long-term use, and the like.

[0008] The present inventors have studied the rubber composition disclosed in Patent Document 1 and have found that a vulcanized rubber obtained by curing the rubber composition may have poor power saving properties.

[0009] Therefore, an object of the present invention is to provide a rubber composition having excellent power saving properties, flex resistance, and flame retardancy after aging of the resulting vulcanized rubber.

[0010] In addition, the present invention also aims to provide a conveyor belt.

[0011] Means for solving problems

[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the problems can be solved by the following configuration.

[0013] [1] A rubber composition comprising:

[0014] Diene rubber including natural rubber and butadiene rubber,

[0015] Flame retardants including chlorinated paraffin and antimony trioxide,

[0016] The specific surface area of ​​nitrogen adsorption is 60 to 100 m 2 / g and a carbon black x1 having a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g,

[0017] Sulfur, and

[0018] Vulcanization accelerator,

[0019] The mass ratio of the natural rubber content to the butadiene rubber content is 50 / 50 to 20 / 80.

[0020] The content of the carbon black X is 55 to 80 parts by mass based on 100 parts by mass of the diene rubber.

[0021] The content of the chlorinated paraffin is 35% by mass or more of the content of the butadiene rubber.

[0022] [2] The rubber composition according to [1], wherein a mass ratio of the content of the vulcanization accelerator to the content of the sulfur is 1.3 or more.

[0023] [3] The rubber composition according to [1] or [2], wherein the mass ratio of the natural rubber content to the butadiene rubber content is 40 / 60 to 30 / 70.

[0024] [4] The rubber composition according to any one of [1] to [3], wherein the carbon black X further comprises a nitrogen adsorption specific surface area of ​​less than 60 m 2 / g and carbon black x2 having a dibutyl phthalate oil absorption of less than 100ml / 100g.

[0025] [5] The rubber composition according to any one of [1] to [4], wherein the content of the carbon black X is 60 to 70 parts by mass based on 100 parts by mass of the diene rubber.

[0026] [6] The rubber composition according to any one of [1] to [5], wherein the content of the chlorinated paraffin is 35 to 50% by mass of the content of the butadiene rubber.

[0027] [7] The rubber composition according to any one of [1] to [6], wherein the content of the antimony trioxide is 8.0% by mass or more of the content of the butadiene rubber.

[0028] [8] The rubber composition according to any one of [1] to [7], further comprising a trimethyldihydroquinoline compound.

[0029] [9] The rubber composition according to any one of [1] to [8], which is for conveyor belts.

[0030]

[10] A conveyor belt produced using the rubber composition described in any one of [1] to [9].

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a rubber composition in which the resulting vulcanized rubber is excellent in power saving, flex resistance, and flame retardancy after aging.

[0033] Furthermore, the present invention may also provide a conveyor belt. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a cross-sectional view of one embodiment of the conveyor belt of the present invention.

[0035] Figure 2 This is a cross-sectional view of another embodiment of the conveyor belt of the present invention. DETAILED DESCRIPTION

[0036] Hereinafter, the present invention will be described in detail.

[0037] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.

[0038] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to".

[0039] In the present specification, each component contained in the rubber composition of the present invention can be used alone or in combination of two or more.

[0040] In the present specification, when the rubber composition of the present invention contains two or more components in combination, the "content" of the component means the total content of the two or more components unless otherwise specified.

[0041] In the present specification, the production method of each component is not particularly limited unless otherwise specified, and examples thereof include conventionally known methods.

[0042] In the present specification, the fact that the obtained vulcanized rubber is more excellent in at least one of power saving performance, flex resistance, and flame retardancy after aging is referred to as "the effect of the present invention is more excellent".

[0043] [Rubber composition]

[0044] The rubber composition of the present invention is the following rubber composition, comprising:

[0045] Diene rubber including natural rubber and butadiene rubber,

[0046] Flame retardants including chlorinated paraffin and antimony trioxide,

[0047] The specific surface area of ​​nitrogen adsorption is 60 to 100 m 2 / g and a carbon black x1 having a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g,

[0048] Sulfur, and

[0049] Vulcanization accelerator,

[0050] The mass ratio of the natural rubber content to the butadiene rubber content is 50 / 50 to 20 / 80.

[0051] The content of the carbon black X is 55 to 80 parts by mass based on 100 parts by mass of the diene rubber.

[0052] The content of the chlorinated paraffin is 35% by mass or more of the content of the butadiene rubber.

[0053] The reason why the rubber composition of the present invention having the above-mentioned structure can solve the problem of the present invention is not necessarily clear, but the present inventors speculate as follows. It should be noted that the mechanism of obtaining the effect is not limited by the following speculation. In other words, the situation where the effect is obtained by a mechanism other than the following is also included in the scope of the present invention.

[0054] The present inventors have confirmed that, in the case where the amount of flame retardant is increased in order to maintain flame retardancy after aging, the flame retardancy after aging can be maintained at the same level as the initial excellent flame retardancy, but the power saving property tends to be worse than that before the amount of flame retardant is increased.

[0055] Furthermore, it was confirmed that the power saving property and / or flex resistance of the obtained vulcanized rubber tend to deteriorate depending on the type and content of carbon black contained in the rubber composition.

[0056] On the other hand, in the present invention, it can be considered that by specifying the mass ratio of the natural rubber content to the butadiene rubber content, the content of carbon black X including carbon black x1, and the content of chlorinated paraffin, the power saving performance, bending resistance, and flame retardancy after aging of the obtained vulcanized rubber can be balanced at an excellent level.

[0057] [Diene rubber]

[0058] In the present invention, the diene rubber contained as the rubber component is a polymer formed by containing a monomer of a conjugated diene compound.

[0059] In the present invention, the diene rubber includes natural rubber and butadiene rubber.

[0060] [Natural rubber]

[0061] In the present invention, the natural rubber (NR) included as the diene rubber is not particularly limited, and examples thereof include conventionally known ones.

[0062] [Butadiene rubber]

[0063] In the present invention, the butadiene rubber (BR) included as the diene rubber is not particularly limited, and examples thereof include conventionally known ones.

[0064] As one of the preferred embodiments, BR is, for example, polybutadiene which is solid at 23° C. In addition, BR may be unmodified BR or modified BR.

[0065] From the viewpoint of achieving more excellent effects of the present invention, the weight average molecular weight of BR is preferably 200,000 or more, more preferably 300,000 to 1,000,000.

[0066] In the present specification, the weight average molecular weight (Mw) of BR may be a standard polystyrene conversion value obtained by gel permeation chromatography (GPC) measurement under the following conditions.

[0067] Solvent: Tetrahydrofuran

[0068] Detector: RI detector

[0069] As one of the preferred embodiments, the diene rubber is preferably natural rubber or butadiene rubber.

[0070] ·Polymers other than diene rubber

[0071] The rubber composition of the present invention may further contain a polymer other than the diene rubber as a rubber component in addition to the diene rubber, but the total content of the natural rubber and the butadiene rubber is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 100% by mass of the total content of the diene rubber and the polymer other than the diene rubber (i.e., the total amount of the rubber component). It should be noted that the polymer other than the diene rubber does not include the trimethyldihydroquinoline compound described below.

[0072] [Mass ratio of natural rubber content to butadiene rubber content]

[0073] In the present invention, the mass ratio of the content of natural rubber to the content of butadiene rubber (content of natural rubber / content of butadiene rubber) is 50 / 50 to 20 / 80.

[0074] When the mass ratio is within the predetermined range, the rubber composition of the present invention is excellent in power saving and bending resistance.

[0075] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and bending resistance), the mass ratio is preferably 40 / 60 to 30 / 70.

[0076] [Flame retardant]

[0077] The rubber composition of the present invention contains a flame retardant comprising chlorinated paraffin and antimony trioxide.

[0078] [Chlorinated paraffin]

[0079] In the present invention, the chlorinated paraffin contained as a flame retardant is a paraffin containing chlorine.

[0080] (Ratio of chlorine in chlorinated paraffin)

[0081] The ratio of chlorine in the chlorinated paraffin is not particularly limited, but is preferably 40 to 90% by mass, more preferably 60 to 80% by mass, in the chlorinated paraffin from the viewpoint of achieving more excellent effects of the present invention.

[0082] [Content of chlorinated paraffin]

[0083] In the present invention, the content of the chlorinated paraffin is 35% by mass or more of the content of the butadiene rubber.

[0084] When the content of the chlorinated paraffin is the above amount, the rubber composition of the present invention has excellent flame retardancy after aging.

[0085] In the present invention, the content of chlorinated paraffin as a flame retardant is set based on the content of the above-mentioned butadiene rubber. Generally speaking, butadiene rubber has lower flame retardancy than natural rubber (i.e., it is easy to burn). On the other hand, in the present invention, the mass ratio of the content of natural rubber to the content of butadiene rubber is 50 / 50 to 20 / 80 (i.e., the content of butadiene rubber is the same as the content of natural rubber, or more than the content of natural rubber). Based on the above situation, the inventors believe that if the content of the flame retardant is set based on the content of diene rubber in the present invention, there is a tendency that the effect of the flame retardant cannot be fully exerted. Therefore, in the present invention, the content of chlorinated paraffin is set based on the content of butadiene rubber. The same is true for the content of antimony trioxide described later.

[0086] From the viewpoint of achieving more excellent effects of the present invention (particularly, flame retardancy after aging), the content of the chlorinated paraffin is preferably 35 to 50% by mass of the content of the butadiene rubber.

[0087] [Antimony trioxide]

[0088] In the present invention, antimony trioxide (Sb 2 O 3 ) contained as a flame retardant is not particularly limited.

[0089] (Antimony trioxide content)

[0090] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and flame retardancy after aging), the antimony trioxide content is preferably 8.0% by mass or more, and preferably 10.0 to 15.0% by mass, based on the content of the butadiene rubber.

[0091] [Carbon Black X]

[0092] The rubber composition of the present invention contains carbon black X. In the present invention, the carbon black X contains carbon black having a nitrogen adsorption specific surface area of ​​60 to 100 m 2 / g and a carbon black x1 having a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g.

[0093] The nitrogen adsorption specific surface area (N2SA) of carbon black can be measured in accordance with JIS K6217-2:2017.

[0094] The dibutyl phthalate oil absorption (DBP) of carbon black can be measured in accordance with JIS K6217-4:2017.

[0095] [Content of Carbon Black X]

[0096] In the present invention, the content of carbon black X (the total content of carbon black contained in the rubber composition of the present invention) is 55 to 80 parts by mass based on 100 parts by mass of the diene rubber.

[0097] When the content of the carbon black X is within a predetermined range, the rubber composition of the present invention is excellent in power saving and bending resistance.

[0098] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and bending resistance), the content of the carbon black X is preferably 60 to 70 parts by mass based on 100 parts by mass of the diene rubber.

[0099] [Carbon Black x1]

[0100] From the viewpoint of achieving a more excellent effect of the present invention, the nitrogen adsorption specific surface area is 60 to 100 m 2 / g and the carbon black x1 having a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g preferably includes HAF grade carbon black.

[0101] As one of the preferred embodiments, all of the carbon black X is carbon black x1.

[0102] ·Content of carbon black x1

[0103] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and bending resistance), the content of carbon black x1 is preferably 55 to 80 parts by mass, more preferably 60 to 70 parts by mass, based on 100 parts by mass of the diene rubber.

[0104] (Carbon Black x2)

[0105] From the viewpoint of further improving the effects of the present invention (particularly power saving, especially power saving at -40°C), the carbon black X further includes a carbon black having a nitrogen adsorption specific surface area of ​​less than 60 m 2 / g and carbon black x2 having a dibutyl phthalate oil absorption of less than 100 ml / 100 g can be cited as one of the preferred embodiments.

[0106] When the carbon black X further includes the carbon black x2, the carbon black x2 preferably includes a GPF grade carbon black from the viewpoint of further improving the effects of the present invention (particularly power saving properties, especially power saving properties at -40°C).

[0107] Carbon black x2 content

[0108] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and bending resistance), the content of the carbon black x2 is preferably 0 to 30 parts by mass based on 100 parts by mass of the diene rubber.

[0109] When the carbon black X further includes carbon black x2, the content of carbon black x2 is preferably 10 to 30 parts by mass based on 100 parts by mass of the diene rubber from the viewpoint of further improving the effects of the present invention (particularly power saving, especially power saving at -40°C).

[0110] Content of carbon black x1 when carbon black x2 is further contained

[0111] When the carbon black X further includes carbon black x2, from the viewpoint that the effects of the present invention (especially, power saving and bending resistance) are better, the content of carbon black x1 is preferably 25 to 70 parts by mass, and more preferably 30 to 60 parts by mass relative to 100 parts by mass of the above-mentioned diene rubber.

[0112] [sulfur]

[0113] The rubber composition of the present invention contains sulfur.

[0114] Sulfur is not particularly limited as long as it is a substance used for vulcanization of rubber, and examples thereof include conventionally known substances.

[0115] [Vulcanization accelerator]

[0116] The rubber composition of the present invention contains a vulcanization accelerator.

[0117] The vulcanization accelerator is not particularly limited as long as it is a substance used for vulcanization of rubber. Examples of the vulcanization accelerator include benzothiazolylsulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazolylsulfenamide (CZ) and N-tert-butyl-2-benzothiazolylsulfenamide (NS); thiuram-based vulcanization accelerators such as tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); guanidine-based vulcanization accelerators such as diphenylguanidine (DPG); and sulfide-based vulcanization accelerators such as dibenzothiazyl disulfide (DM) and 4,4'-dithiomorpholine.

[0118] From the viewpoint of achieving better effects of the present invention (particularly power saving), the vulcanization accelerator preferably contains a benzothiazolylsulfenamide vulcanization accelerator and / or a guanidine vulcanization accelerator, and more preferably contains a benzothiazolylsulfenamide vulcanization accelerator and a guanidine vulcanization accelerator.

[0119] (Value of mass ratio of content of vulcanization accelerator / content of sulfur)

[0120] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and bending resistance), the value of the mass ratio of the content of the vulcanization accelerator / the content of sulfur is preferably 1.3 or more, more preferably 1.4 to 1.9.

[0121] (Sulfur content)

[0122] From the viewpoint of achieving more excellent effects of the present invention (particularly, power saving and flex resistance), the sulfur content is preferably 0.5 to 5.0 parts by mass, more preferably 1.0 to 3.0 parts by mass, based on 100 parts by mass of the diene rubber.

[0123] (Content of vulcanization accelerator)

[0124] From the viewpoint of achieving better effects of the present invention (particularly power saving and bending resistance), the content of the vulcanization accelerator (when two or more vulcanization accelerators are used, the total content of these vulcanization accelerators) is preferably 0.5 to 8.0 parts by mass, more preferably 1.0 to 3.0 parts by mass, relative to 100 parts by mass of the diene rubber.

[0125] (Trimethyldihydroquinoline compounds)

[0126] From the viewpoint of achieving more excellent effects of the present invention (particularly flame retardancy and flex resistance after aging), one of the preferred embodiments of the rubber composition of the present invention is to further contain a trimethyldihydroquinoline compound.

[0127] As the above-mentioned trimethyldihydroquinoline compounds, for example, polymers of 2,2,4-trimethyl-1,2-dihydroquinoline (compounds of the structure in [] in the following formula) shown in the following formula can be cited. It should be noted that the compounds shown in [] below are shown as monomers. The polymer of 2,2,4-trimethyl-1,2-dihydroquinoline refers to a polymer of 2,2,4-trimethyl-1,2-dihydroquinoline (monomer) or more. n (number of repeating units) in the following formula is 2 or more.

[0128]

[0129] ·Weight average molecular weight of trimethyldihydroquinoline compounds

[0130] The weight average molecular weight of the trimethyldihydroquinoline compound is preferably not less than 300. The upper limit of the weight average molecular weight is preferably not more than 1,000.

[0131] In the present specification, the weight average molecular weight (Mw) of the trimethyldihydroquinoline compound may be a standard polystyrene conversion value obtained by gel permeation chromatography (GPC) measurement under the following conditions.

[0132] Solvent: Tetrahydrofuran

[0133] Detector: RI detector

[0134] ·Content of trimethyldihydroquinoline compounds

[0135] When the rubber composition of the present invention further contains a trimethyldihydroquinoline compound, the content of the trimethyldihydroquinoline compound is preferably 1.0 to 10.0 parts by mass, more preferably 2.0 to 5.0 parts by mass, relative to 100 parts by mass of the above-mentioned diene rubber, from the viewpoint that the effects of the present invention (particularly flame retardancy and flex resistance after aging) are more excellent.

[0136] (additive)

[0137] The rubber composition of the present invention may further contain additives in addition to the above-mentioned components. Examples of the additives include antioxidants such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6C), oils such as aromatic oils, waxes, zinc oxide, stearic acid, and vulcanization retarders (e.g., N-cyclohexylthiophthalimide).

[0138] One of the preferred embodiments is that the rubber composition of the present invention does not contain a hydrazide compound. The hydrazide compound is not particularly limited as long as it is a compound having a group represented by -CO-NHN.

[0139] (Manufacturing method)

[0140] The method for producing the rubber composition of the present invention is not particularly limited, and one example includes a method of mixing the above essential components and, if necessary, additives using a Banbury mixer or the like at 90 to 180°C.

[0141] (vulcanization)

[0142] The vulcanization of the rubber composition of the present invention can be carried out under the conditions usually performed. The vulcanization temperature can be, for example, 120 to 180° C. During the vulcanization, pressure may be applied.

[0143] (use)

[0144] As an application of the rubber composition of the present invention, for example, a rubber composition for conveyor belts can be mentioned.

[0145] [conveyor]

[0146] The conveyor belt of the present invention is a conveyor belt produced using the rubber composition of the present invention.

[0147] The rubber composition used for the conveyor belt of the present invention is not particularly limited as long as it is the rubber composition of the present invention.

[0148] The conveyor belt of the present invention is not particularly limited except that it is produced using the rubber composition of the present invention.

[0149] Since the conveyor belt of the present invention is produced using the rubber composition of the present invention, it is excellent in power saving, bending resistance, and flame retardancy after aging.

[0150] There is no particular limitation on which component of the conveyor belt of the present invention the rubber composition of the present invention is applied to. The rubber composition of the present invention can be used to manufacture all or part of the rubber constituting the conveyor belt of the present invention.

[0151] Since the vulcanized rubber obtained by curing the rubber composition of the present invention is excellent in power saving, flex resistance, and flame retardancy after aging, the conveyor belt of the present invention having a covering rubber formed using the rubber composition of the present invention can be cited as one of the preferred embodiments.

[0152] Embodiments of the conveyor belt of the present invention will be described below using the accompanying drawings. It should be noted that the present invention is not limited to the accompanying drawings.

[0153] Figure 1 This is a cross-sectional view of one embodiment of the conveyor belt of the present invention. Figure 1 One embodiment of the conveyor belt of the present invention shown (herein, also referred to as the first embodiment of the conveyor belt of the present invention) is a conveyor belt 4 in which a fabric layer 1 is coated with a coating rubber (adhesive rubber) 2 to form a core material layer, and the outer periphery thereof is covered with a covering rubber 3. The covering rubber 3 is preferably formed using the rubber composition of the present invention.

[0154] exist Figure 1 In the embodiment, the conveyor belt 4 has the fabric layer 1 as the core material, and the number of laminated layers of the fabric layer 1, the thickness of the covering rubber 3, the belt width, etc. can be appropriately determined according to the purpose of use.

[0155] Examples of the cloth layer include canvas made of woven fabric of synthetic fibers such as nylon, vinylon, and polyester.

[0156] The thicknesses T1 and T2 of the cover rubber 3 may be approximately 1.5 to 20 mm, respectively, under normal circumstances.

[0157] In addition, coating rubber 2 can use coating rubber used for known conveyor belts. As the coating rubber, for example, a rubber composition containing natural rubber (NR), nitrile rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), ethylene-propylene rubber (EPT), ethylene-propylene-diene rubber (EPDM), etc. as a rubber component can be used.

[0158] Next, use Figure 2 A second embodiment of the conveyor belt of the present invention will be described.

[0159] Figure 2 This is a cross-sectional view of another embodiment of the conveyor belt of the present invention.

[0160] like Figure 2 As shown, the second embodiment of the conveyor belt of the present invention is a conveyor belt 8 in which a steel cord 5 is coated with a cushion rubber (adhesive rubber) 6 to form a core layer, and the outer periphery thereof is covered with a covering rubber 7. The covering rubber 7 is preferably formed using the rubber composition of the present invention.

[0161] The conveyor belt 8 may be made of, for example, 50 to 230 steel cords 5 having a diameter of about 2.0 to 9.5 mm, which are obtained by twisting a plurality of strands having a diameter of about 0.2 to 0.4 mm. Generally, the total thickness T of the conveyor belt 8 may be about 10 to 50 mm.

[0162] In addition, the buffer rubber 6 may use, for example, an adhesive rubber that can be bonded to the galvanized steel cord used in a known steel conveyor belt. Specifically, as the buffer rubber, for example, a rubber composition containing natural rubber (NR), nitrile rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), etc. as a rubber component may be used.

[0163] The conveyor belt of the present invention can be manufactured, for example, by placing a cloth layer, steel cord, or core material layer, which is a core material, between unvulcanized rubber sheets molded from the rubber composition of the present invention according to a conventional method, and vulcanizing them by heating and pressing. The vulcanization conditions can be, for example, about 120 to 180° C. and about 0.1 to 4.9 MPa for about 10 to 90 minutes.

[0164] The conveyor belt of the present invention can be used at a temperature of, for example, -50 to +60°C.

[0165] Example

[0166] The present invention will be described in further detail below based on examples.

[0167] The materials, usage amounts, ratios, processing contents, and processing steps shown in the following examples may be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0168] <Manufacturing of rubber composition>

[0169] The components shown in Table 1 below were used in the compositions (parts by mass) shown in the table, and these were mixed using a Banbury mixer at 90 to 180° C. to produce rubber compositions (unvulcanized).

[0170] <Evaluation>

[0171] The following evaluations were performed using each rubber composition prepared as described above. The results are shown in the tables.

[0172] (Power saving)

[0173] ·Test piece preparation

[0174] Each rubber composition (unvulcanized) prepared as described above was vulcanized for 30 minutes under normal vulcanization conditions at a surface pressure of 3.0 MPa using a press molding machine at 148° C. to prepare a vulcanized rubber sheet 1 (initial) having a length of 150 mm, a width of 150 mm, and a thickness of 2 mm.

[0175] From each vulcanized rubber sheet 1 (initial) produced as described above, a vulcanized sheet having a size of 40 mm in length, 5 mm in width, and 2 mm in thickness was punched out to produce a test piece for evaluating power saving performance.

[0176] Evaluation method

[0177] Using each test piece prepared as described above, dynamic viscoelasticity measurement was performed using a viscoelastic spectrometer (manufactured by Toyo Seiki Seisaku-sho, Ltd.) under the measurement conditions of 10 mm between chucks, 2% dynamic strain, and 20 Hz frequency, and the loss tangent (tanδ) and dynamic elastic modulus E' (N / mm) at -40°C, -20°C, and 0°C were measured. The obtained loss tangent (tanδ) and dynamic elastic modulus E' were substituted into the following formula to obtain RRF (Rolling Resistance Factor). In the present invention, RRF is used to evaluate power saving.

[0178]

[0179] The RRF results at each temperature are expressed as indices, with the RRF results at each temperature of Comparative Example 3 being 100. The results (indexes) at each temperature are shown in the "power saving" column of each table.

[0180] Evaluation benchmark

[0181] When the RRF (index) of the obtained vulcanized rubber at -40°C, -20°C, and 0°C was less than 100, the obtained vulcanized rubber was evaluated to be excellent in power saving property.

[0182] The smaller the RRF index at each temperature, the better the power saving performance.

[0183] On the other hand, when any one of the RRF (index) at -40°C, -20°C, and 0°C of the obtained vulcanized rubber was 100 or more, the obtained vulcanized rubber was evaluated to be inferior in power saving property.

[0184] (Bending resistance)

[0185] Evaluation method

[0186] A crack growth test by repeated bending was performed in accordance with the bending crack growth test described in JIS K6260:2017.

[0187] Specifically, each composition was vulcanized for 30 minutes at 148°C and a surface pressure of 3.0 MPa to produce a test piece described in "5.1" of JIS K6260:2017. A test piece of the size specified in the above-mentioned bending crack extension test was made, and the test piece with the cut introduced by the specified cutting blade was subjected to a bending resistance test using a Demacia bending tester (temperature: 23°C, stroke: 40mm, speed: 300±10rpm, total number of bending times: 400,000 times). After the test, the length of the crack was measured. The results are shown in the "Bending Resistance (Crack Extension)" column of each table.

[0188] Evaluation benchmark

[0189] When the length of the crack is 30 mm or less, the obtained vulcanized rubber is evaluated to have excellent bending resistance. In addition, the smaller the length of the crack is than 30 mm, the more excellent the bending resistance is.

[0190] On the other hand, when the length of the crack exceeded 30 mm, it was evaluated that the bending resistance of the obtained vulcanized rubber was poor.

[0191] (Flame retardancy after aging)

[0192] ·Test piece preparation

[0193] Using each rubber composition produced as described above, test pieces (9 test pieces each) were produced according to JIS K6324:2013 "Flame retardant performance conveyor belt - Grades and test methods (Flame retardant performance conveyor belt - Grades and test methods)" 7.2.1. During the vulcanization of the above production, a press molding machine was used at 148°C, and the surface pressure was 3.0 MPa under normal vulcanization conditions for 30 minutes to obtain a BL sample (blank sample).

[0194] Three of the nine BL samples obtained as described above were used to perform an aging test under conditions of 100° C. for 168 hours, thereby obtaining samples after the 168-hour aging test.

[0195] Three of the nine BL samples obtained as described above were subjected to an aging test at 100° C. for 336 hours, thereby obtaining samples after the 336-hour aging test.

[0196] Evaluation method of flame retardancy

[0197] Regarding BL samples (3 pieces), samples after 168 hours of aging test (3 pieces), and samples after 336 hours of aging test (3 pieces), the flame duration (unit: seconds) was measured in accordance with JIS K6324:2013 "Flame retardant performance conveyor belts-Grades and test methods (Flame retardant performance conveyor belts-Grades and test methods)".

[0198] Evaluation criteria for flame retardancy of BL samples and samples after aging test

[0199] In the present invention, when the BL sample satisfies the JIS 3 grade flame retardancy test standard [the duration of the flame is within 1 minute (the duration of the flame is the average of 3 test pieces), and there is no re-burning], it is evaluated as having excellent initial flame retardancy, which is indicated as "0".

[0200] On the other hand, when the BL sample did not satisfy the flame retardancy test standard of JIS Class 3, it was evaluated that the initial flame retardancy was poor, which was indicated by "×".

[0201] The evaluation criteria for the flame retardancy of the samples after the 168-hour and 336-hour aging tests were also the same as the evaluation criteria for the flame retardancy of the BL sample.

[0202] The evaluation results of the flame retardancy of the BL samples are shown in the "Flame Retardancy BL" column in the table.

[0203] The evaluation results of the flame retardancy of the samples after the 168-hour aging test are shown in the "Flame Retardancy AG1" column in the table.

[0204] The evaluation results of the flame retardancy of the samples after the 336-hour aging test are shown in the "Flame Retardancy AG2" column in the table.

[0205] Evaluation criteria for flame retardancy after aging

[0206] In the present invention, when the initial flame retardancy is excellent (the "Flame Retardancy BL" column in the table is indicated as "○") and the "Flame Retardancy AG1" column in the table is "○", it is evaluated that the flame retardancy after aging is excellent.

[0207] In addition, when the "Flame retardation BL" column, the "Flame retardation AG1" column, and the "Flame retardation AG2" column in the table are all "○", it is evaluated that the flame retardancy after aging is more excellent.

[0208] On the other hand, when the initial flame retardancy was excellent (the "Flame Retardancy BL" column in the table was ○), but the flame retardancy after aging was poor (the "Flame Retardancy AG1" column in the table was "×"), the flame retardancy after aging was evaluated to be poor.

[0209] In this specification, when the initial flame retardancy is poor ("Flame retardancy BL" column in the table is "x"), since the original flame retardancy is poor, the above case is treated as a case where the flame retardancy after aging is poor.

[0210] [Table 1]

[0211]

[0212] [Table 2]

[0213]

[0214] [Table 3]

[0215]

[0216] [Table 4]

[0217]

[0218] The details of each component shown in each table are as follows.

[0219] (Diene rubber)

[0220] NR: Natural rubber. RSS#3

[0221] BR: Butadiene rubber. Trade name: Nipol BR1220 (weight average molecular weight: 460,000, manufactured by Japan Zeon Co., Ltd.)

[0222] (Carbon Black X)

[0223] ·HAF grade CB: Trade name: Syst N, manufactured by Shin Nichia Carbon Co., Ltd. N2SA: 74m 2 / g, DBP: 101cm 3 / 100g

[0224] The above-mentioned HAF grade CB is equivalent to carbon black x1.

[0225] ·GPF grade CB: Trade name Nitron #55S (Nitron #55S), manufactured by Nippon Steel Carbon Co., Ltd. N2SA: 26m 2 / g, DBP: 88cm 3 / 100g

[0226] The above-mentioned GPF-grade CB is equivalent to carbon black x2.

[0227] ·ISAF grade CB: The trade name is Shaw Black N220 (ショウブラックN220), manufactured by Cabot Japan Co., Ltd. N2SA: 111m 2 / g, DBP: 115cm 3 / 100g

[0228] The above-mentioned ISAF grade CB does not correspond to carbon black x1 and x2.

[0229] (Flame Retardant)

[0230] Chlorinated paraffin: Enpara 70S manufactured by Dow Chemical Co., Ltd. (trade name). Chlorine content 68-72% by mass. Average Cl content 70% by mass. The chlorine content in the chlorinated paraffin was calculated using the average Cl content of 70% by mass.

[0231] · Antimony trioxide: PATOX-M manufactured by Nippon Seiko Co., Ltd. (trade name)

[0232] (Antioxidant)

[0233] 6C (molecular weight: 268): amine antioxidant. N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (structure shown below). Trade name: Ozonone 6C (manufactured by Seiko Chemical Co., Ltd.). 6C has the following structure.

[0234]

[0235] (Trimethyldihydroquinoline compounds)

[0236] RD (weight average molecular weight: 400-600): A polymer of 2,2,4-trimethyl-1,2-dihydroquinoline (structure shown below). Trade name: Nonflex RD (manufactured by Seiko Chemical Industries, Ltd.).

[0237] Weight average molecular weight 400~600

[0238]

[0239] (additive)

[0240] Zinc oxide: Zinc oxide. Trade name: "Zinc oxide III (Oxidized sub-lead 3 types)" (manufactured by Shodo Chemical Industry Co., Ltd.).

[0241] · St.: stearic acid. Trade name: "Stearic acid 50S" (manufactured by Chiba Fatty Acid Co., Ltd.)

[0242] (Vulcanization accelerator)

[0243] Vulcanization accelerator NS: N-tert-butyl-2-benzothiazolylsulfenamide (trade name: Noxella NS, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)

[0244] Vulcanization accelerator D: diphenylguanidine (trade name: Noxelara D, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)

[0245] (Vulcanizing agent)

[0246] Sulfur: insoluble sulfur. MUCRON OT-20S manufactured by Shikoku Chemical Industry Co., Ltd. (trade name). Sulfur concentration: 80% by mass. The content shown in the column "Sulfur" in Table 1 is the amount of the insoluble sulfur.

[0247] From the results in Table 1, it was confirmed that the rubber composition of the present invention exhibited the desired effects.

[0248] On the other hand, in Comparative Example 1 in which the content of carbon black did not satisfy the prescribed range and no flame retardant was contained, the flame retardancy after aging was poor.

[0249] Comparative Examples 2 and 3, in which the carbon black content was less than the prescribed range, had poor power saving properties. Comparative Example 4, in which the carbon black content exceeded the prescribed range, had poor power saving properties and poor bending resistance.

[0250] Does not contain carbon black x1, but instead contains nitrogen adsorption surface area exceeding 100m 2 In Comparative Example 5 in which the carbon black had an average carbon black content of 0.1 wt. % and 0.1 wt. % respectively, the bending resistance was poor.

[0251] In Comparative Example 6, in which the mass ratio of the content of natural rubber to the content of butadiene rubber was outside the prescribed range, the power saving property was poor.

[0252] In Comparative Example 7, in which the mass ratio of the natural rubber content to the butadiene rubber content was outside the prescribed range and the chlorinated paraffin content was less than 35 mass % of the butadiene rubber content, the flex resistance and flame retardancy after aging were poor.

[0253] In Comparative Example 8, in which the mass ratio of the content of natural rubber to the content of butadiene rubber was outside the prescribed range, power saving and bending resistance were inferior.

[0254] In Comparative Example 9, in which the content of the chlorinated paraffin was less than 35% by mass of the content of the butadiene rubber, the flame retardancy after aging was poor.

[0255] Explanation of symbols

[0256] 1: Fabric layer

[0257] 2: Coating rubber

[0258] 3,7: Covering rubber

[0259] 4, 8: Conveyor belt

[0260] 5: Steel cord

[0261] 6: Buffer rubber.

Claims

1. A rubber composition comprising: Diene rubber including natural rubber and butadiene rubber, Flame retardants including chlorinated paraffin and antimony trioxide, The specific surface area of ​​nitrogen adsorption is 60 to 100 m 2 / g and a carbon black x1 having a dibutyl phthalate oil absorption of 90 ml / 100 g or more and less than 140 ml / 100 g, Sulfur, and Vulcanization accelerator, The mass ratio of the natural rubber content to the butadiene rubber content is 50 / 50 to 20 / 80, The content of the carbon black X is 55 to 80 parts by mass relative to 100 parts by mass of the diene rubber. The content of the chlorinated paraffin is 35% by mass or more of the content of the butadiene rubber. 2 . The rubber composition according to claim 1 , wherein a value of a mass ratio of the content of the vulcanization accelerator to the content of the sulfur is 1.3 or more. 3 . The rubber composition according to claim 1 , wherein a mass ratio of the natural rubber content to the butadiene rubber content is 40 / 60 to 30 / 70.

4. The rubber composition according to claim 1, wherein the carbon black X further comprises a nitrogen adsorption specific surface area of ​​less than 60 m 2 / g and carbon black x2 having a dibutyl phthalate oil absorption of less than 100ml / 100g. 5 . The rubber composition according to claim 1 , wherein the content of the carbon black X is 60 to 70 parts by mass based on 100 parts by mass of the diene rubber. 6 . The rubber composition according to claim 1 , wherein the content of the chlorinated paraffin is 35 to 50% by mass based on the content of the butadiene rubber. 7 . The rubber composition according to claim 1 , wherein the content of the antimony trioxide is 8.0% by mass or more based on the content of the butadiene rubber. 8 . The rubber composition according to claim 1 , further comprising a trimethyldihydroquinoline compound. 9 . The rubber composition according to claim 1 , which is for a conveyor belt. 10 . A conveyor belt produced using the rubber composition according to claim 1 .